Тривимірні матричні суперпотенціали - Караджов, Ю.А. (Український математичний журнал, 2012)
Представлена классификация матричных суперпотенциалов, которые соответствуют точно решаемым системам уравнений Шредингера. Рассмотрены суперпотенциалы вида Wk=kQ+P+R*(1/k), где k — параметр, P,Q и R — эрмитовые матрицы, зависящие от переменной x. Список трехмерных матричных суперпотенциалов приведен в явном виде. We present a classification of matrix superpotentials that correspond to exactly solvable systems of Schrödinger equations. Superpotentials of the form Wk=kQ+P+R*(1/k) are considered, where k is a parameter and P, Q, and R are Hermitian matrices that depend on a variable x. The list of three-dimensional matrix superpotentials is presented in explicit form.